Topical Fermented Lactobacillus acidophilus Lysate Accelerates Second-Degree Burn Healing: An In Vivo Study in Wistar Rats - Kamilah, Lian; Kusumawardani, Arie; Widhiati, Suci; Dharmawan, Nugrohoaji; Ellistasari, Endra Yustin (HM Publisher, 2025)
Second-degree burns, affecting the epidermis and dermis, constitute a major category of thermal injuries globally, presenting significant clinical challenges including pain, infection risk, and potential scarring. While standard treatments like silver sulfadiazine (SSD) exist, limitations including potential cytotoxicity and emerging resistance necessitate exploration of novel therapeutic strategies. Recent interest has focused on topical applications derived from probiotics, such as Lactobacillus spp., due to their suggested roles in modulating inflammation, combating oxidative stress, and providing antimicrobial activity to accelerate wound repair. This study investigated a fermented lysate derived from Lactobacillus acidophilus (L. fermented) as a potential topical agent for burn healing. This study aimed to evaluate the therapeutic efficacy of a 5% topical L. fermented ointment on the healing process of experimentally induced second-degree burns in a Wistar rat model, primarily by assessing the rate of wound closure compared to standard SSD treatment and an untreated control. A true experimental in vivo study utilizing a post-test only control group design was performed following ethical approval. Fifteen male Wistar rats were subjected to a standardized second-degree thermal burn injury on their dorsal aspect. The animals were then randomized (n=5 per group) to receive twice-daily topical applications of either 5% L. fermented ointment (Group A), SSD ointment (Group B), or no treatment (Control, Group C). Wound healing was quantitatively assessed by measuring the wound surface area (mm²) on days 1, 3, 7, and 14 post-injury using digital imaging and ImageJ software analysis. Statistical comparisons between groups were conducted using one-way ANOVA followed by LSD post-hoc tests, with statistical significance set at p<0.05. All treatment groups demonstrated a significant reduction in wound size over the 14-day observation period (p=0.001 within each group). Inter-group comparisons revealed significantly accelerated wound closure in Group A starting from day 3 onwards (p<0.005). At day 14, the mean wound area in Group A (17.5 ± 8.06 mm²) was significantly smaller than in Group B (119.22 ± 45.41 mm²) and Group C (305.18 ± 25.21 mm²) (p=0.001). Post-hoc analysis confirmed the superiority of L. fermented treatment over both SSD (mean difference 101.72 mm², p=0.001) and control (mean difference 287.68 mm², p=0.001). SSD treatment also resulted in significantly better healing than the control group (mean difference 185.96 mm², p=0.001). In conclusion, topical application of 5% fermented Lactobacillus acidophilus lysate significantly accelerated the closure of second-degree burn wounds in Wistar rats, demonstrating superior efficacy compared to both silver sulfadiazine treatment and no treatment. These findings highlight the potential of L. fermented lysate as a promising novel therapeutic agent for burn wound management.